The Efficacy of Shatyadhi Churna in the Management of Vataja Pratisyaya (Allergic Rhinitis) in Children: A Randomized Controlled Clinical Trial - Aparna Dileep; Mahapatra Arun Kumar; Rajagopala Shrikrishna (Wolters Kluwer Medknow Publications, 2024)
Introduction:Allergic rhinitis (AR), clinically compatible with Vataja pratisyaya, is a highly prevalent global health issue that has a substantial negative effect on quality of life, especially children. In the text Basavarajiyam, Shatyadhi churna is mentioned in the treatment of Pratisyaya (~rhinitis) to be taken along with Ghrita and Guda. The study was undertaken with the objective to evaluate the efficacy of Shatyadhi churna in Vataja pratisyaya w. r. t AR among children of 6-16 year age in comparison with syrup Levocetirizine (LCZ).Methods:Ethically approved trial was two-arm, randomized, open-labeled, controlled, parallel, interventional study with allocation ratio 1:1, conducted at All India Institute of Ayurveda (AIIA), New Delhi on outpatient department basis.Results:In the present study, out of total 30 enrolled participants, 16 patients were assigned to intervention group, Shatyadhi churna (trial period of 4 weeks) and 14 others were assigned to control group, Syrup LCZ (trial period of 2 weeks). Treatment with the trial drug significantly reduced the clinical features, immunoglobulin E level and improved the health-related quality of life among the participants.Conclusion:The anti-inflammatory, antihistamine, analgesic, antioxidant properties and Dipana (digestion enhancer), Ama pachana (metabolism enhancer), Anulomana (regularizing physiological movement), Srotoshodhaka (cleansing of functional channels) and Rasayana (rejuvenation) attributes of each individual drugs are responsible for Doshapratyanika (treatment specified to regulatory functional factors of body) as well as Vyadhipratyanika chikitsa (disease specific treatment) of Shatyadhi churna in the management of Vataja pratisyaya w. r. t AR.